Pengaruh environmental accounting dan firm size terhadap nilai perusahaan - Anissa, Anna; Soegiarto K, Eddy; Sonaria, Mita (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2023)
This study aims to determine and analyze the effect of environmental accounting and firm size on firm value. The research population is construction sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The research sample was taken using a purposive sampling technique. The data used is quantitative data. This study uses panel data regression analysis. The results showed that environmental accounting and firm size simultaneously affect firm value. Partially, environmental accounting has no effect and firm size has a negative effect on firm value.